Epidemiological study of the KALA-AZAR cases in Iraq for the years - Abid, Baqir Kareem (The Iraqi Journal of Veterinary Medicine, 2004)
study of KALA-AZAR cases in Iraq was conducted during July 2004 , to study the epidemiological distribution of KALA-AZAR cases in Iraq for the years (1999-2003) comparing it with the cases of the previous years (1994-1998). Data were collected from the communicable diseases control "CDC" center of Baghdad with detailed information of age, gender, time and seasonal distribution, which recorded for the last years (1999-2003) , also with data of the KALA-AZAR cases for the previous years (1994-1998), while the data concerning study population was obtained from the planning directorate of MOH depending on the last cansus reports of 1997 , most of the Iraqi governorates were included (except the self-rule’s governorate). The different governorates were categorized according to the number of KALA-AZAR cases and to their geographical position.